High-adaptability conductive paste, preparation method thereof and application of conductive paste in carbon-coated current collector
By coating carbon materials with RnSiX(4-n), a highly adaptable conductive paste was prepared, which solved the problems of uneven coating and poor adhesion caused by the difference in residual oil content of aluminum foil, and achieved uniform spreading and strong adhesion of the conductive paste on various aluminum foils.
Patent Information
- Application Number
- CN202510784882.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-12
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2045-06-12
AI Technical Summary
Different manufacturers use cleaning solutions with different compositions and cleaning purposes, resulting in large differences in the amount of residual oil on aluminum foil. This affects problems such as uneven coating distribution, missed coating, and poor coating adhesion. Existing corona treatment methods have limited effectiveness.
A highly adaptable conductive paste was prepared by coating modified carbon materials with RnSiX(4-n), which improved the spreadability, dispersibility and adhesion properties, and formed a conductive coating.
It significantly improves the spreadability, dispersibility and adhesion of conductive paste on aluminum foil, solves the problems of uneven coating distribution and poor adhesion, and is suitable for aluminum foil in various oily conditions.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of new energy technology, and more specifically, it relates to a highly adaptable conductive paste, its preparation method, and its application in carbon-coated current collectors. Background Technology
[0002] Carbon-coated current collectors are composite materials composed of foil and conductive materials coated on the surface. As a key component of batteries, they are widely used in electrochemical energy storage devices such as lithium-ion batteries and sodium-ion batteries. Their quality directly affects the overall performance of the battery.
[0003] During the production process, aluminum foil materials can become contaminated with oil, impurities, and other pollutants, making the cleaning process crucial. However, due to differences in the composition of cleaning solutions and the purpose of cleaning used by different manufacturers, the amount of residual oil on aluminum foil varies greatly, which is detrimental to downstream processing.
[0004] In related technologies, such as CN202310888585.4, corona treatment is used to replace cleaning of aluminum foil. However, the surface oil stains of the treated aluminum foil still vary greatly. Therefore, downstream manufacturers still have problems such as uneven coating distribution, missed coating, poor coating adhesion and peeling when reprocessing. In summary, to overcome the negative impact of foil material differences on its performance, this application provides a highly adaptable conductive paste, its preparation method, and its application in carbon-coated current collectors. Summary of the Invention
[0005] To overcome the negative impact of foil material differences on actual performance, this application provides a highly adaptable conductive paste, its preparation method, and its application in carbon-coated current collectors. By pretreating the carbon material, the spreadability, dispersibility, and adhesion of the paste on aluminum foil are significantly improved, making it suitable for aluminum foils of most specifications and in oily conditions.
[0006] In a first aspect, this application provides a highly adaptable conductive paste, employing the following technical solution: A highly adaptable conductive paste is composed of the following components in the indicated weight ratios: Modified carbon material 3.6-7.2%; binder 4.5-8%; balance is solvent; The modified carbon material is carbon material coated with material R. n SiX (4-n) Obtained by coating; The coating material R n SiX (4-n) In this context, R represents a non-hydrolyzable organic functional group, X represents a hydrolyzable group, and n ranges from 1 to 3.
[0007] By adopting the above technical solution, carbon material is coated with material Rn SiX (4-n) The modified carbon material obtained by coating is obtained through R n SiX (4-n) The coating modification takes into account excellent spreadability, dispersibility and adhesion properties, and can be used for most foil materials with oily surface conditions. Considering both practical application effects and the single variable of composition, the underlying principle may be as follows: 1) Its improved spreadability and dispersibility are due to the chemical bonding and physical adsorption effect between the R group and the surface of the carbon material, which effectively reduces the agglomeration of carbon particles and makes the slurry more uniform. 2) The improved adhesion is mainly due to the reaction of hydrolyzed groups (X) with functional groups on the aluminum foil surface to form an interface bridge, which in turn significantly improves the bonding force between the coating and the substrate (adhesion ≥ 5B).
[0008] Preferably, the carbon material and the coating material R n SiX (4-n) The weight ratio is 1:(0.002-0.06).
[0009] By adopting the above technical solution, the coating rate of the modified carbon material under this ratio is balanced and controlled, ensuring that the surface of the carbon material is fully covered without redundant coating. It is not easy for the conductivity to be hindered by excessive coating agent, nor is it easy for the dispersibility to decrease due to insufficient coating.
[0010] Preferably, the non-hydrolyzable organic functional group is selected from methyl, vinyl, amino, epoxy, mercapto, or acryloyloxypropyl.
[0011] By adopting the above technical solution, the selected non-hydrolyzable organic functional groups can all combine with the surface defect sites of carbon materials, thereby ensuring the stability of the coating layer. In addition, amino and acryloyloxypropyl groups are also beneficial to the subsequent slurry compatibility and curing crosslinking effect.
[0012] Preferably, the hydrolyzed group is selected from alkoxy, aryloxy, acyloxy, polyurethane, acrylic, -CH2CH2O-, n-vinylamide, phthalic acid, -NH-CO-O- (carbamate), and -NCO (isocyanate).
[0013] By adopting the above technical solution, the selected hydrolytic groups take into account both the controllability of hydrolysis and the cross-section enhancement effect. In addition to the moderate hydrolysis rate, which is not easy to cause uneven coating due to excessive reaction, some hydrolysis will also generate hydroxyl groups, which will condense with the hydroxyl groups on the aluminum foil surface, thereby improving the adhesion.
[0014] Preferably, the coating material R n SiX (4-n) Specifically, it is aminotriethoxysilane.
[0015] Secondly, this application provides a method for preparing the aforementioned highly adaptable conductive paste, comprising the following steps: S1. First, disperse the carbon material in the coating material and ultrasonically treat it for 10-30 minutes; S2. Stir and react at 60-80℃ for 1-3 hours to form a uniform slurry; S3. Then, the slurry is centrifuged and dried to obtain the modified carbon material; S4. Mix the modified carbon material obtained in S3 with solvent and binder in the corresponding weight ratio, and ball mill until the particle size is ≤1μm to obtain conductive paste.
[0016] By adopting the above technical solution, the preparation process is significantly simplified while maintaining high controllability. All conditions are easy to operate and achieve, which is conducive to the stability and fullness of the product, and can effectively meet the needs of conductive paste and its application in current collectors.
[0017] Thirdly, this application provides an application of the conductive paste described in any one of the above claims or the conductive paste obtained by the above preparation method in a carbon-coated current collector, using the following technical solution: The process includes the following steps: coating the conductive paste onto the surface of an aluminum foil, drying it at 80-150℃, and then curing it to form a conductive coating with a thickness of 0.01-10μm.
[0018] Fourthly, this application provides a highly adaptable carbon-coated current collector, comprising an aluminum foil substrate and a coating formed by the conductive paste described in any one of the above-mentioned methods or the conductive paste obtained by the above-mentioned preparation method.
[0019] Fifthly, this application provides an energy storage device comprising the aforementioned carbon-coated current collector.
[0020] Sixthly, this application provides a modified carbon material, employing the following technical solution: A modified carbon material, comprising a carbon material and a coating material R n SiX (4-n) The mixture was prepared by blending and modification at a weight ratio of 1:(0.002-0.06), and the specific steps are as follows: A1. First, disperse the carbon material in the coating material and sonicate for 10-30 minutes; A2. Stir and react at 60-80℃ for 1-3 hours to form a uniform slurry; A3. Then, the slurry is centrifuged and dried to obtain the modified carbon material; The coating material R n SiX (4-n) The value of n in the equation ranges from 1 to 3. R is a non-hydrolyzable organic functional group selected from methyl, vinyl, amino, epoxy, mercapto, or acryloyloxypropyl. X is a hydrolyzable group selected from alkoxy, aryloxy, acyloxy, polyurethane, acrylic, -CH2CH2O-, n-vinylamide, phthalic acid, -NH-CO-O- (carbamate), and -NCO (isocyanate).
[0021] By adopting the above technical solution, carbon material is coated with material R n SiX (4-n) The modified carbon material obtained by coating has excellent chemical bonding and physical adsorption effects under the action of the coating layer, and is not prone to carbon particle agglomeration. It is suitable for any field that requires the dispersion of carbon materials.
[0022] In summary, this application has the following beneficial effects: 1. This application uses carbon material coated with material R n SiX (4-n) The modified carbon material obtained by coating is obtained through R n SiX (4-n) The coating modification takes into account excellent spreadability, dispersibility and adhesion properties, and can be used for most foil materials with oily surface conditions. 2. The preparation process in this application is significantly simplified while being highly controllable. All conditions are easy to operate and achieve, which is conducive to the stability of the product and the fullness of the reaction, and can effectively meet the needs of conductive paste and its application in current collectors. 3. The carbon material in this application is coated with material R n SiX (4-n) The modified carbon material obtained by coating has excellent chemical bonding and physical adsorption effects under the action of the coating layer, and is not prone to carbon particle agglomeration. It is suitable for any field that requires the dispersion of carbon materials. Detailed Implementation
[0023] The present application will be further described in detail below with reference to the embodiments.
[0024] Preparation Examples 1-5 A modified carbon material, comprising a carbon material and a coating material R n SiX (4-n) The mixture was prepared by blending and modification according to the corresponding weight parts in the table below. The specific steps are as follows: A1. First, disperse the carbon material in the coating material and sonicate for 20 minutes; The carbon material is carbon black with a particle size of 200 nm; A2. Stir and react at 65℃ for 2 hours to form a uniform slurry; A3. Then, the slurry is centrifuged and dried to obtain the modified carbon material; The coating material R n SiX (4-n) In this context, n is 1, R is a non-hydrolyzable organic functional group selected from methyl, and X is a hydrolyzable group selected from alkoxy-methoxy. n SiX (4-n) The coating material is specifically methyltrimethoxysilane.
[0025] Table: Components and their corresponding weights (kg) in Preparation Examples 1-5
[0026] Preparation Examples 6-10 A modified carbon material, differing from preparation example 3 in that the coating material R... n SiX (4-n) The usage scenarios differ, as shown in the table below: Table: Selection of Coating Material RnSiX(4-n) in Preparation Examples 6-10
[0027] The conductive pastes prepared in the examples and comparative examples were selected as the test objects, and the obtained conductive pastes were coated on aluminum foils with a thickness of 2 μm (oil stains of A, B and C, respectively). Aluminum foil A: oil content is 2mg / m 2 ; Aluminum foil B: Oil content is 5mg / m³ 2 ; Aluminum foil C: Oil content is 10mg / m³ 2 ; After drying at 120℃ and curing, a conductive coating with a thickness of 1μm was formed. Then, the coating adhesion, conductivity, missing coating rate, and dispersibility were tested. The specific testing standards and procedures are as follows: Coating adhesion test: Use a blade to draw a 1mm×1mm orthogonal grid on the coating surface (depth to the aluminum foil substrate), and test the coating on different areas with different loads. Apply the special tape (3M 600 type) to the grid area, press firmly, and then peel it off vertically and quickly. Observe the proportion of the peeled area under a microscope. For specific testing standards, refer to ASTM D3359 cross-cut test.
[0028] Conductivity test: A four-terminal electrode resistance meter (ACCF-G2A) was used at a pressure of 25MPa. Five points were tested in the area, and the average value was taken after removing outliers. The diaphragm resistance was measured in accordance with the standard ASTM F390.
[0029] Missing coating rate test: Randomly select a 10cm×10cm coating area, scan the surface with a terahertz micrometer probe (resolution ≤5μm) to identify the exposed areas of aluminum foil without slurry coverage, and calculate the percentage of missing coating area: Missing coating rate = Exposed area / Total test area X 100%.
[0030] Dispersion uniformity test: Take the cured carbon-coated current collector and randomly select 5 fields of view (×50000). Observe it by transmission electron microscopy (TEM) to count the size and spacing of carbon particle agglomeration, and count as uniform, obvious agglomeration and local agglomeration. Refer to standard GB / T 21868.3 for details. Example
[0031] Examples 1-5 A highly adaptable conductive paste, the components and their corresponding weights are shown in the table below: Table: Components and their corresponding weights (kg) in Examples 1-5
[0032] The modified carbon material was prepared by dispersing and mixing the components at 1500 r / min for 20 min at room temperature. The modified carbon material was prepared by Preparation Example 3, the binder was acrylic resin (CAS No. 9003-01-4), and the solvent was water.
[0033] Comparative Example 1 A conductive paste differs from Example 1 in that its modified carbon material is replaced by an equal amount of carbon material (carbon black with a particle size of 200 nm), while all other aspects are the same as in Example 1.
[0034] Comparative Example 2 A conductive paste differs from Example 1 in that its modified carbon material is replaced by an equal amount of carbon material (the carbon material is carbon black with a particle size of 200 nm), and the aluminum foil before coating is corona treated by a single 8KW corona machine with a total of 4 sets at a speed of 80 m / min.
[0035] Comparative Example 3 A conductive paste, which differs from Example 1 in that the amount of modified carbon material used is 1.8 kg, while all other aspects are the same as in Example 1.
[0036] Conductive pastes prepared in Examples 1-5 and Comparative Examples 1-3 were extracted and tested according to the above measurement steps and standards to measure the coating adhesion, conductivity, missing coating rate and dispersibility on different aluminum foil (A / B / C) surfaces. The average value of the test results was recorded in Tables 1-4 below.
[0037] Table 1: Results of Coating Adhesion Performance Test
[0038] Table 2: Test results of conductivity properties
[0039] Table 3: Results of Missing Coating Rate Detection
[0040] Table 4: Results of Dispersion Uniformity Test
[0041] As can be seen from Tables 1-4 above, the highly adaptable conductive pastes prepared in Examples 1-5 have excellent spreadability, dispersibility and adhesion properties, and can be used on most foils with oily surfaces (refer to aluminum foil A, aluminum foil B and aluminum foil C in this application). The highly adaptable conductive pastes in Examples 1-5 of this application in Table 1 have an adhesion of ≥4B when applied to any of aluminum foils A, B, and C. Comparative Examples 1-2, which used conventional carbon materials, still showed adhesion performance ≤4B when applied to aluminum foils B and C with highly oily surfaces, even after corona treatment. As for Comparative Example 3, the amount of modified carbon material used was too low, resulting in performance that could not meet expectations.
[0042] The highly adaptable conductive pastes in Examples 1-5 of this application in Table 2 have a resistance of 1.98-2.76 (mΩ), which is an improvement to varying degrees compared to Comparative Examples 1-2 using ordinary carbon materials and Comparative Example 3 with insufficient carbon material. Moreover, this performance is not related to the oil stains on the aluminum foil surface, but only to the coating omission rate.
[0043] The highly adaptable conductive pastes in Examples 1-5 of this application, as shown in Table 3, have a coating omission rate of ≤1.8% when applied to any of aluminum foils A, B, and C. Comparative Examples 1-2, which used conventional carbon materials, still had a coating failure rate of ≥6.1% when applied to aluminum foils A, B, and C, even after corona treatment. As for Comparative Example 3, the amount of modified carbon material used was too low, resulting in its performance failing to meet expectations.
[0044] Table 4 shows that the highly adaptable conductive pastes in Examples 1-5 of this application exhibit uniform dispersion when applied to any of aluminum foils A, B, and C, showing a significant improvement compared to Comparative Examples 1-3. They are not easily affected by the choice of aluminum foil (i.e., differences in surface oil stains).
[0045] In summary, the highly adaptable conductive paste of this application is preferably composed of the following components in the following weight ratio: 3.6-7.2% modified carbon material; 4.5-8% binder; and the balance being solvent. Any adjustment within the above range can yield a stable and uniform conductive paste. Based on the data from each group, the underlying principle can be deduced as follows: 1) Its improved spreadability and dispersibility are due to the chemical bonding and physical adsorption effect between the R group and the surface of the carbon material, which effectively reduces the agglomeration of carbon particles and makes the slurry more uniform. 2) The improved adhesion is mainly due to the reaction of hydrolyzed groups (X) with functional groups on the aluminum foil surface to form an interface bridge, which in turn significantly improves the bonding force between the coating and the substrate (adhesion ≥ 5B).
[0046] Furthermore, the data in the table above also shows that: carbon materials are coated with material R n SiX (4-n) The modified carbon materials prepared by coating have excellent chemical bonding and physical adsorption properties under the action of the coating layer, and are not prone to carbon particle agglomeration. They are suitable for any field that requires the dispersion of carbon materials.
[0047] Examples 6-9 A highly adaptable conductive paste differs from Example 1 in that the use of modified carbon material is different, and the specific correspondence is shown in the table below.
[0048] Table: Comparison of the use of modified carbon materials in Examples 6-9
[0049] The conductive pastes prepared in Examples 6-9 were extracted and tested according to the above measurement steps and standards to measure the coating adhesion, conductivity, missing coating rate and dispersibility on different aluminum foil (A / B / C) surfaces. The average value of the test results was recorded in Tables 5-8 below.
[0050] Table 5: Results of Coating Adhesion Performance Test
[0051] Table 6: Test Results of Conductivity Performance
[0052] Table 7: Results of Missing Coating Rate Detection
[0053] Table 8: Results of Dispersion Uniformity Test
[0054] As can be seen from Tables 5-8 above, the highly adaptable conductive pastes prepared in Examples 6-9 have a certain degree of spreadability, dispersibility and adhesion performance, and can be used for most foil materials with oily surfaces (refer to aluminum foil A, aluminum foil B and aluminum foil C in this application). In Table 5, only the highly adaptable conductive pastes in Examples 8-9 of this application have an adhesion of ≥5B when applied to any of aluminum foils A, B, and C. As for Examples 6-7, due to the adjustment of the component ratio, the coating rate is unbalanced, resulting in the performance not achieving the expected effect.
[0055] In Table 6, only the highly adaptable conductive pastes in Examples 8-9 of this application have good conductivity, with a resistance of 2.4-2.6 (mΩ). Compared with Examples 6-7, which had an unbalanced ratio, they all showed varying degrees of improvement, and this performance was independent of the oil stains on the aluminum foil surface.
[0056] Table 7 shows that the high-adaptability conductive paste in Examples 8-9 of this application has a coating failure rate of ≤1.5% when applied to any of aluminum foils A, B, and C. As for Examples 6-7, due to the adjustment of the component ratio, the coating rate is unbalanced, resulting in the performance also failing to meet the expected effect.
[0057] Table 8 shows that only the highly adaptable conductive pastes in Examples 8-9 of this application exhibit uniform dispersion when applied to any of aluminum foils A, B, and C. Examples 6-7 also show no agglomeration, indicating that they are not easily affected by differences in the oil stains on the aluminum foil surface.
[0058] In summary, carbon materials and coating materials R n SiX (4-n) The preferred weight ratio is 1:(0.002-0.06). Only with this ratio can the coating rate of the modified carbon material be balanced and controlled, ensuring that the carbon material surface is fully covered without redundant coating. This prevents the conductivity from being hindered by excessive coating agent, while also preventing the dispersibility from decreasing due to insufficient coating.
[0059] Examples 10-14 A highly adaptable conductive paste differs from Example 1 in that the use of modified carbon material is different, and the specific correspondence is shown in the table below.
[0060] Table: Comparison of the use of modified carbon materials in Examples 10-14
[0061] The conductive pastes prepared in Examples 10-14 were extracted and tested according to the above measurement steps and standards to measure the coating adhesion, conductivity, missing coating rate and dispersibility on different aluminum foil (A / B / C) surfaces. The average value of the test results was recorded in Tables 9-12 below.
[0062] Table 9: Results of Coating Adhesion Performance Test
[0063] Table 10: Test Results of Conductivity Performance
[0064] Table 11: Results of Missing Coating Rate Detection
[0065] Table 12: Results of Dispersion Uniformity Test
[0066] As can be seen from Tables 9-12 above, the highly adaptable conductive pastes prepared in Examples 10-14 possess at least one of the following properties: spreadability, dispersibility, and adhesion. They can be used on most foils with oily surfaces (refer to aluminum foil A, aluminum foil B, and aluminum foil C in this application). Its theoretical basis stems from the modification analysis and derivation of carbon materials, as detailed below: 1) The selected non-hydrolyzable organic functional groups can all combine with the surface defect sites of carbon materials to ensure the stability of the coating layer. In addition, amino and acryloyloxypropyl groups are also beneficial to the subsequent slurry compatibility and curing crosslinking effect.
[0067] 2) The selected hydrolytic groups take into account both the controllability of hydrolysis and the cross-section enhancement effect. In addition to the moderate hydrolysis rate, which is not easy to cause uneven coating due to excessive reaction, some hydrolysis will also generate hydroxyl groups, which will condense with the hydroxyl groups on the aluminum foil surface, thereby improving the adhesion.
[0068] However, the aforementioned coating material R n SiX (4-n) When put into practical use, discrepancies were found between theory and practice. Only Example 10 exhibited excellent performance across the board. The possible reasons for this are as follows: Example 11, namely Preparation Example 7, when the coating material R n SiX (4-n) When n is 2, specifically when it is dimethyldiacetoxysilane, its conductivity decreases significantly. It is speculated that the reason is that the acetoxy group undergoes hydrolysis, which in turn triggers localized acid corrosion of the carbon material.
[0069] Example 12, namely Preparation Example 8, when the coating material R n SiX (4-n) When n is 2, specifically when it is methylvinyldimethoxysilane, its adhesion decreases significantly, especially when applied to aluminum foil B and aluminum foil C. The reason is speculated to be that vinyl tends to form a cross-linked network, which is too rigid and thus restricts the release of interfacial stress of carbon materials, making them prone to peeling.
[0070] Example 13, namely Preparation Example 9, when the coating material R n SiX (4-n)When n is 3, specifically trimethylaminosilane, its dispersibility is poor and carbon material agglomeration is very likely to occur. It is speculated that the reason is that the amino group has low density and large steric hindrance, which affects the binding with carbon material, resulting in uneven coating of carbon material and thus affecting the dispersion effect.
[0071] Example 14, namely Preparation Example 10, when the coating material R n SiX (4-n) When n is 3, specifically when it is triphenylethoxysilane, its conductivity is also affected and significantly increased. It is speculated that the reason is that the relative volume of phenyl is too large, which hinders the movement of molecular chain segments, thus causing the continuous damage to the conductive network and is not conducive to the coverage of its coating layer.
[0072] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A highly adaptable conductive paste, characterized in that, It consists of components in the following weight ratios: Modified carbon material 3.6-7.2%; binder 4.5-8%; balance is solvent; The modified carbon material is carbon material coated with material R. n SiX (4-n) The carbon material and the coating material R are obtained by coating. n SiX (4-n) The weight ratio is 1:(0.002-0.06); The coating material R n SiX (4-n) In this context, R represents a non-hydrolyzable organic functional group, X represents a hydrolyzable group, and n ranges from 1 to 3. The preparation method of the highly adaptable conductive paste includes the following steps: S1. First, disperse the carbon material in the coating material and sonicate for 10-30 minutes; S2. Stir and react at 60-80℃ for 1-3 hours to form a uniform slurry; S3. Then, the slurry is centrifuged and dried to obtain the modified carbon material; S4. Mix the modified carbon material obtained in S3 with solvent and binder in the corresponding weight ratio, and ball mill until the particle size is ≤1μm to obtain conductive paste.
2. The highly adaptable conductive paste according to claim 1, characterized in that, The non-hydrolyzable organic functional group is selected from methyl, vinyl, amino, epoxy, mercapto, or acryloyloxypropyl.
3. The highly adaptable conductive paste according to claim 1, characterized in that, The hydrolyzable groups are selected from alkoxy, aryloxy, acyloxy, polyurethane, acrylic, -CH2CH2O-, n-vinylamide, phthalic acid, carbamate (-NH-CO-O-), and isocyanate (-NCO).
4. The highly adaptable conductive paste according to claim 1, characterized in that, The coating material R n SiX (4-n) Specifically, it is aminotriethoxysilane.
5. The application of the conductive paste according to any one of claims 1-4 in a carbon-coated current collector, characterized in that, Includes the following steps: The conductive paste is coated onto the surface of aluminum foil, dried at 80-120℃ and then cured to form a conductive coating with a thickness of 0.5-3μm.
6. A highly adaptable carbon-coated current collector, characterized in that, The coating includes an aluminum foil substrate and a conductive paste as described in any one of claims 1-4.
7. An energy storage device, characterized in that, It includes the carbon-coated current collector as described in claim 6.
8. A modified carbon material, characterized in that, Composed of carbon materials and coating material R n SiX (4-n) The mixture was prepared by blending and modification at a weight ratio of 1:(0.002-0.06), and the specific steps are as follows: A1. First, disperse the carbon material in the coating material and sonicate for 10-30 minutes; A2. Stir and react at 60-80℃ for 1-3 hours to form a uniform slurry; A3. Then, the slurry is centrifuged and dried to obtain the modified carbon material; The coating material R n SiX (4-n) The value of n in the equation ranges from 1 to 3. R is a non-hydrolyzable organic functional group selected from methyl, vinyl, amino, epoxy, mercapto, or acryloyloxypropyl. X is a hydrolyzable group, which is selected from alkoxy, aryloxy, acyloxy, polyurethane, acrylic, -CH2CH2O-, n-vinylamide, phthalic acid, urethane (-NH-CO-O-), and isocyanate (-NCO).
Citation Information
Patent Citations
Battery aluminum foil and method for manufacturing the same
CN116851443B
Carbon-coated current collector and preparation method thereof
CN119965276A
